Answer:
(x, y) = (10, 2)
Step-by-step explanation:
given the 2 equations
x = 8 + y → (1)
x - 11y = - 12 → (2)
rearrange (2) expressing x in terms of y ( add 11y to both sides )
x = - 12 + 11y → (3)
(1) and (3) both express x in terms of y, hence we can equate the right sides
- 12 + 11y = 8 + y ( subtract y from both sides )
- 12 + 10y = 8 ( add 12 to both sides )
10y = 20 ( divide both sides by 10 )
y = 2
substitute y = 2 into either (1) or (3) for value of x
(1) → x = 8 + 2 = 10
solution is (10, 2 )